2015
DOI: 10.1007/s12031-015-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Improvement Induced by Environment Enrichment in Chronic Cerebral Hypoperfusion Rats: a Result of Upregulated Endogenous Neuroprotection?

Abstract: Environment enrichment (EE) has been demonstrated to improve the cognitive impairment that is induced by chronic cerebral hypoperfusion (CCH), but the underlying mechanism has not yet been elucidated. This study aimed to investigate the role of endogenous neuroprotection in EE-induced cognitive improvement in rats with CCH. Permanent bilateral common carotid artery occlusions (2-vessel occlusions (2VOs)) were performed to induce CCH in male adult Wistar rats. Four weeks after the surgeries, the rats were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
12
1
1
Order By: Relevance
“…Chronic cerebral hypoperfusion (CCH) is a prevalent pathophysiological state in patients with Alzheimer's disease (AD) and vascular dementia (VaD). CCH has been identified as one of the initial conditions that are critical in the development of cognitive dysfunction [193].…”
Section: Chronic Hypoxia and Brain Responsementioning
confidence: 99%
“…Chronic cerebral hypoperfusion (CCH) is a prevalent pathophysiological state in patients with Alzheimer's disease (AD) and vascular dementia (VaD). CCH has been identified as one of the initial conditions that are critical in the development of cognitive dysfunction [193].…”
Section: Chronic Hypoxia and Brain Responsementioning
confidence: 99%
“…Oxidative stress has been strongly correlated to the pathogenesis of VaD (Liu and Zhang, ; Yang et al, ). Excess reactive oxygen and nitrogen species generated following excitotoxic insults induce significant changes in redox status associated with oxidative damage to cellular and vascular structures, in which protein oxidation, cleavage of DNA, and inhibition of the mitochondrial electron transport chain are the main features (Calabrese et al, ; Di Marco et al, ).…”
Section: Mitochondrial Dysfunction Inflammasomes and Neuroinflammatmentioning
confidence: 99%
“…Although the mechanisms whereby EE preserves cognition remain obscure, numerous studies have suggested that the functional improvement related to EE is associated with the up-regulation of neurotrophic factors, the enhancement of synaptic plasticity, and the stimulation of neurogenesis [28], and the reduction of apoptosis and oxidative damage [29,30]. Learning and memory processes linked to differentiating PV interneuron networks can be regulated by recent experience, suggesting that EE may modulate cognition by targeting the differentiation state of PV neurons in the adult [31].…”
Section: Discussionmentioning
confidence: 99%